Preoperative cervical sagittal alignment parameters and their impacts on myelopathy in patients with cervical spondylotic myelopathy: a retrospective study - Yuan, Wei; Zhu, Yue; Zhu, Haitao; Cui, Cui; Pei, Lei; Huang, Zhuxi (PeerJ, 2017)
Background Cervical sagittal alignment plays an important role in the pathogenesis of cervical spondylotic myelopathy (CSM), but there are limited studies on the cervical sagittal parameters in CSM patients and their correlations with myelopathy. The aim of this study is to investigate the correlations among the preoperative cervical sagittal alignment parameters and their correlations with the development of myelopathy in patients with CSM. Methods We retrospectively collected 212 patients with CSM who underwent surgical interventions. Gender, age, modified Japanese Orthopedic Association score (mJOA), cervical lordosis (CL), C2–C7 sagittal vertical axis (C2–C7 SVA), T1 slope (T1S), neck tilt (NT) and thoracic inlet angle (TIA) were collected before operation. Interobserver and intraobserver reliability were calculated for all measurements (intraclass correlation coefficient, ICC). Data were analyzed with Pearson and Spearman correlation tests and multiple linear regression analysis. Results A total of 212 patients with CSM were included in this study (male: 136, female: 76) with an average age of 54.5 ± 10.1 years old. Intraobserver and interobserver reliability for all included radiographic parameters presented good to excellent agreement (ICC > 0.7). No significant differences in demographic and radiological parameters have been observed between males and females (P > 0.05). We found statistically significant correlations among the following parameters: age with CL (r = 0.135, P = 0.049), age with T1S (r = 0.222, P = 0.001), CL with T1S (r = 0.291, P < 0.001), CL with C2-C7 SVA (r = − 0.395, P < 0.001), mJOA with age (r = − 0.274, P < 0.001), mJOA with C2–C7 SVA (r = − 0.219, P < 0.001) and mJOA with T1S(r = − 0.171, p = 0.013). Linear regression analysis showed that C2–C7 SVA was the predictor of CL (adjusted R2 = 0.152, P < 0.001) and multiple linear regression showed that age combined with C2–C7 SVA was a sensitive predictor of mJOA (adjusted R2 = 0.106, P < 0.001). Discussion There were significant correlations among certain preoperative cervical sagittal parameters in CSM patients. CL was the only predictor of C2–C7 SVA. Age combined with C2–C7 SVA could predict the severity of myelopathy.
Keywords: Cervical lordosis; Sagittal vertical axis; Myelopathy; Cervical sagittal alignment; mJOA